PPR water supply heat preservation pipe and preparation method thereof
By adding glass microspheres to reinforce aerogel composite particles in PPR resin, a porous-cavity composite thermal insulation network is formed, which solves the problem of PPR water supply pipes being prone to cracking at low temperatures, improves structural stability and thermal insulation performance, and enhances the durability and thermal insulation effect of the pipe material.
Patent Information
- Application Number
- CN202511247356.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-09-03
AI Technical Summary
Traditional PPR water supply pipes are prone to cracking or developing micro-cracks under low-temperature conditions, leading to leaks and seepage, which affects the normal operation and service life of the pipeline system. Existing insulation measures have problems with interface delamination and poor durability.
Glass microsphere-reinforced aerogel composite particles are compounded with PPR resin. By adding glass microsphere-reinforced aerogel composite particles to PPR resin, a porous-cavity composite thermal insulation network is formed, which enhances the interfacial bonding force and structural stability. Silane coupling agents are used to improve interfacial compatibility and mechanical strength.
This technology improves the overall structural strength and insulation performance of PPR water supply insulation pipes, maintains stable insulation effects over a long period, solves the problems of interface defects and poor durability of the outer insulation layer, and enhances the overall performance of the pipe material.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of pipe materials, in particular to a PPR water supply heat preservation pipe and a preparation method thereof. BACKGROUND
[0002] In many fields such as building, municipal, industrial and agricultural irrigation, the PPR water supply pipe has been more and more applied due to its advantages of energy saving and material saving, environmental protection, light weight and high strength, corrosion resistance, smooth inner wall without scaling, simple construction and maintenance and long service life. Whether it is the water supply and drainage system inside the building, the large-scale water supply and drainage pipe network in urban and rural areas, or the construction of industrial fluid conveying and agricultural irrigation pipeline, the PPR water supply pipe plays a key role. When the traditional PPR water supply pipe is faced with cold environment, its limitations are exposed. Under low temperature conditions, the pipe body is prone to cracking or producing fine cracks, thereby causing leakage and seepage problems, which seriously affect the normal operation and service life of the pipeline system. In order to solve this problem, various heat preservation measures for PPR water supply pipes have appeared in the market, among which coating the heat preservation material on the PPR pipe is a common way, for example, using polyurethane, rock wool, rubber and plastic and other heat preservation materials to wrap outside the PPR pipe through adhesive bonding or mechanical fixing.
[0003] The patent application file with the publication number CN103851273A discloses a water supply pipeline with PPR-PVC, which is composed of a PPR pipe, a polyurethane rigid foam heat preservation layer and a PVC protective shell. The polyurethane rigid foam is foamed and integrally formed into the heat preservation layer, which fills the gap between the inner core pipe and the PVC protective shell. At the connection between the pipelines, the elbow and the tee, the inner core pipe is connected by socket heat melting, and then the polyurethane is foamed on site to form an integrally formed heat preservation layer. Finally, the PVC protective shell is tightly fastened and fixed by screws. Although the scheme realizes the overall formation of the heat preservation layer by on-site foaming and socket heat melting connection, the difference in the thermal expansion coefficient between the PPR pipe and the polyurethane rigid heat preservation layer is prone to produce microcracks. Oxygen permeating along the cracks will accelerate the aging of PPR and reduce its durability. SUMMARY
[0004] In order to improve the durability of the PPR water supply heat preservation pipe, the application provides a PPR water supply heat preservation pipe and a preparation method thereof.
[0005] In the first aspect, the application provides a PPR water supply heat preservation pipe, which adopts the following technical scheme,
[0006] A PPR water supply heat preservation pipe, which comprises the following raw materials by weight: 75-85 parts of PPR resin, 15-25 parts of glass bead reinforced aerogel composite particles and 0.1-0.3 parts of silane coupling agent.
[0007] The preparation method of the glass microsphere reinforced aerogel composite particle is as follows: mixing hollow glass microspheres with an ethanol solution containing a silane coupling agent, heating and reacting, and vacuum drying to obtain activated microspheres; adding a silica aerogel precursor to the activated microspheres, adjusting the pH to 9-10, and reacting to form a gel; and after aging, hydrophobic treatment, and drying, crushing to obtain glass microsphere reinforced aerogel composite particles.
[0008] By adopting the above technical scheme, the PPR water supply heat preservation pipe is prepared by adding the glass microsphere reinforced aerogel composite particle to the PPR resin, there is no interface delamination problem, the structure has strong integrity, has a single homogeneous structure, and the material is uniform and consistent, and the stable heat preservation performance can be maintained for a long time; the interface hidden danger of the outer heat preservation layer, the complex construction, the poor durability, the space limitation and other problems are fundamentally solved, and the stable heat preservation effect can be ensured for a long time.
[0009] In particular, the glass microsphere reinforced aerogel composite particle prepared in the application uses hollow glass microspheres as a mechanical skeleton to compensate for the brittleness defect of aerogel, and the closed cavity structure helps to improve the overall heat preservation performance; at the same time, the aerogel is filled in the gap between the microspheres to form a porous-cavity composite heat insulation network, which improves the heat preservation performance of the prepared PPR water supply heat preservation pipe.
[0010] Preferably, the silica aerogel precursor is a silica sol with a particle size of 10-20 nm and a solid content of 15%-25%.
[0011] By adopting the above technical scheme, the nanoparticles of the silica sol can be closely combined with the active groups on the surface of the activated microspheres to form a uniform bridging structure; the solid content can ensure that enough silica sol fills the gap between the microspheres to enhance the interfacial bonding strength, and at the same time, the light weight property of the glass microsphere reinforced aerogel composite particle is not damaged due to excessive amount; at the same time, the high reactivity of the nanoparticles can promote the formation of a continuous and stable three-dimensional network of the composite system, which takes into account the mechanical strength and heat insulation performance of the composite material, and the low cost of the silica sol and the process adaptability are more conducive to the large-scale preparation of high-performance composite heat insulation materials.
[0012] Preferably, the mass ratio of the silica aerogel precursor to the activated microspheres is (1-5):(1-3).
[0013] By adopting the above technical scheme, if the proportion of activated microspheres is too high, the silica cannot fully fill the gap between the hollow glass microspheres, resulting in weak interfacial bonding strength and a loose composite structure formed by the two; if the proportion of activated microspheres is too low, the cavity heat insulation advantage of the hollow glass microspheres is weakened, and excessive silica aerogel precursor may generate stress due to drying shrinkage, which damages the composite structure.
[0014] Preferably, the hydrophobic treatment specifically comprises dissolving the modifier in a solvent to obtain a modified solution, and soaking the aged gel in the modified solution to obtain the hydrophobic gel.
[0015] The addition amount of the modifier is 5-20wt% of the gel; the modifier is one of hexamethyldisilazane, trimethylchlorosilane and methyltrioxysilane; and the solvent is one of anhydrous ethanol, n-hexane and cyclohexane.
[0016] By using the above technical solution, the surface of the gel is covered with hydrophobic groups, which can not only ensure the structural stability during drying, but also enable the final glass microsphere reinforced aerogel particles to have long-term moisture resistance and water resistance, thereby expanding their application in high humidity environments.
[0017] Preferably, the supercritical drying method is used during drying, specifically comprising: placing the aged gel in a high-pressure reaction kettle, adding anhydrous ethanol to cover the gel, and replacing the air in the kettle with nitrogen; placing the reaction kettle in a low-temperature environment of 3-8℃, injecting liquid CO2 through a high-pressure pump to a pressure of 5-7MPa, and after standing for 40-80min, discharging the mixed liquid containing ethanol, and repeatedly injecting and discharging multiple times; increasing the temperature to 32-40℃ and adding CO2 to make the pressure reach 8-10MPa, maintaining for 1.5-3h, then reducing to normal pressure at a rate of 0.1-0.3MPa / h, and taking out the gel after natural cooling.
[0018] By using the above technical solution, the supercritical drying method is a high-efficiency method for avoiding the collapse of aerogel pores, which uses supercritical fluid to remove the solvent in the gel, avoids the structural shrinkage or collapse caused by interfacial tension during drying, and can maximize the preservation of the porous network of silica aerogel and the cavity structure of hollow glass microspheres, thereby ensuring the low thermal conductivity and lightweight characteristics of the material.
[0019] Preferably, the hollow glass microspheres are plasma-treated hollow glass microspheres.
[0020] By using the above technical solution, the surface of the hollow glass microspheres can form active groups such as hydroxyl and carboxyl groups after plasma treatment, which can undergo grafting reaction with silane coupling agents, so that the groups of the silane coupling agents are anchored on the surface of the hollow glass microspheres, which is beneficial to forming a firm structure with the aerogel network and is not easy to fall off under the pressure change and temperature conditions of supercritical drying.
[0021] Preferably, the hollow glass microsphere is a double-cavity hollow glass microsphere, and the preparation method is as follows: 100 parts by weight of borosilicate glass powder, 15-20 parts by weight of a double-cavity template agent, 1-2 parts by weight of a dispersing agent, and 200-300 parts by weight of deionized water are ball milled for 2-4 hours to form a slurry; the slurry is added to a spray drying machine at a feeding rate of 5-10 mL / min, and is atomized into droplets under the conditions of 15000-20000 rpm, air inlet temperature of 200-220 DEG C, and air outlet temperature of 80-100 DEG C, and the precursor microspheres are formed after drying; the precursor microspheres are first degreased at 600-650 DEG C for 2-3 hours under nitrogen protection, and then are fused and sintered at 1200-1300 DEG C for 1-2 hours, and are naturally cooled to room temperature to obtain the double-cavity hollow glass microspheres.
[0022] By adopting the above technical scheme, the interpenetrating network formed by the double-cavity hollow glass microspheres and the silica aerogel can reduce local stress concentration and improve tensile strength, compared with the interpenetrating network of the single-cavity microsphere system, by virtue of the multi-node stress dispersion, double-cavity synergistic deformation resistance, and enhanced interface anchoring effect of the double-cavity structure; in terms of thermal conductivity, the double thermal resistance, more tortuous heat conduction path, and reduced thermal bridge effect between the microspheres formed by the double cavities can reduce the thermal conductivity and improve the heat preservation performance of the prepared PPR water supply heat preservation pipe.
[0023] Preferably, 0.2-0.4 parts by weight of a nucleating agent is further included.
[0024] By adopting the above technical scheme, the addition of an appropriate amount of the nucleating agent can promote the formation of fine and uniform crystals of PPR during the cooling process, improve the crystallinity of the pipe material, and thus enhance the mechanical properties thereof.
[0025] Preferably, the nucleating agent is a mixture of a sorbitol alpha nucleating agent and a rare earth beta nucleating agent in a mass ratio of 1: (1-3).
[0026] By adopting the above technical scheme, the alpha nucleating agent is mainly used to improve the crystallization rate and crystallinity of PPR, and the beta nucleating agent is mainly used to induce the formation of beta crystal form of PPR and improve the low-temperature toughness of the material; the compounding of the sorbitol alpha nucleating agent and the rare earth beta nucleating agent in the PPR water supply heat preservation pipe can realize the balance of rigidity and toughness and improve the mechanical properties and heat resistance of the pipe material through the synergistic effect of crystal forms.
[0027] In a second aspect, the application provides a preparation method of a PPR water supply heat preservation pipe, which adopts the following technical scheme,
[0028] The preparation method of the PPR water supply heat preservation pipe comprises the following steps:
[0029] The raw materials are weighed according to the formula and uniformly mixed to obtain a mixture, the mixture is melt-extruded and granulated to obtain a composite master batch; the composite master batch is melted and extruded through a mold and then cooled and shaped to obtain a PPR water supply heat preservation pipe.
[0030] In summary, the present application has the following beneficial effects:
[0031] 1、The glass microsphere reinforced aerogel composite particles of the present application take hollow glass microspheres as the mechanical skeleton, and aerogel is filled in the interstices of the microspheres to form a porous-cavity composite heat insulation network, and the PPR water supply pipe prepared by compounding the network with PPR resin has good heat preservation effect, and compared with the traditional method of coating heat preservation materials on the PPR pipe, the structure has higher integrity and longer service life.
[0032] 2、The present application performs plasma treatment on the hollow glass microspheres, and the plasma treatment can make the silane coupling agent more efficiently and more uniformly grafted to the surface of the glass microspheres, one end of the silane coupling agent is combined with the glass microspheres through a chemical bond, and the other end is reacted with the aerogel precursor through a functional group to form a strong interface combination of glass microspheres-silane coupling agent-aerogel, and finally improve the mechanical strength, structural stability and interface compatibility of the composite particles.
[0033] 3、The glass microsphere reinforced aerogel composite particles of the present application form an interpenetrating network through the interpenetrating network of the double-cavity hollow glass microspheres and the silica aerogel, and in terms of mechanical strength, the interpenetrating network of the double-cavity structure has more nodes for stress dispersion, synergistic deformation resistance and enhanced interface anchoring effect, and can reduce local stress concentration and improve tensile strength compared with the interpenetrating network of the single-cavity microsphere system; in terms of thermal conductivity, the double thermal resistance formed by the double cavities, the more tortuous heat conduction path and the reduced thermal bridge effect between the microspheres make the thermal conductivity coefficient decrease, and improve the comprehensive performance of the prepared PPR water supply heat preservation pipe. DETAILED DESCRIPTION
[0034] The present application will be further described in detail below in combination with examples.
[0035] The raw materials of the examples and comparative examples of the present application are all ordinary commercially available, except for special instructions.
[0036] Glass microsphere reinforced aerogel composite particles of preparation examples 1-7
[0037] Preparation example 1
[0038] The present preparation example discloses a preparation method of glass microsphere reinforced aerogel composite particles, which specifically comprises the following steps:
[0039] (1) Take 100 g of hollow glass microspheres with a particle size of 10-30 μm, add 500 mL of anhydrous ethanol, and ultrasonically clean for 30 min under a power of 300 W; after filtration, rinse twice with deionized water, and vacuum dry at 0.09 MPa vacuum degree and 60°C for 2 h to obtain pretreated glass microspheres; add 300 mL of anhydrous ethanol to a three-necked flask, slowly add 3 g of KH550 at a rate of 1 drop / s under stirring, add 5 mL of deionized water, adjust the pH of the system to 4 with 0.1 mol / L hydrochloric acid, and continue stirring for 10 min to obtain a coupling agent solution; add the pretreated glass microspheres to the coupling agent solution, heat to 70°C, and react for 3 h under 300 rpm magnetic stirring; after the reaction is completed, filter, rinse three times with anhydrous ethanol, and transfer to a vacuum drying oven, and dry at 60°C and 0.09 MPa for 4 h to obtain activated microspheres;
[0040] (2) Slowly pour 60 g of silica sol with a particle size of 10-20 nm and a solid content of 20% into 40 g of activated microspheres at a rate of 5 mL / min, magnetically stir at a speed of 400 rpm for 30 min, and add 25 wt% ammonia water at a rate of 2 drops / s while stirring, adjust the pH of the system to 9.5, keep at room temperature, continue stirring for 10 min, and then transfer to a polytetrafluoroethylene mold, seal with a cover, and stand at room temperature for 2 h to obtain a composite wet gel;
[0041] (3) mixed deionized water and absolute ethanol with a volume ratio of 9:1 to obtain an aging solution; 20 g of the composite wet gel was completely immersed in 100 mL of the aging solution, sealed and placed in a 60 °C constant temperature water bath, and aged for 24 h (the aging solution was replaced every 8 h during the aging process) to obtain a composite gel; 100 mL of absolute ethanol was taken, 3 g of hexamethyldisilazane was added, and the mixture was stirred uniformly to obtain a modifier solution; in a fume hood, the composite gel was rinsed with absolute ethanol twice, transferred to the modifier solution, and reacted at 50 °C under magnetic stirring at a rotation speed of 200 rpm for 4 h; after the reaction was completed, the product was soaked with absolute ethanol three times, each time for 100 mL for 2 h, to obtain a hydrophobic composite gel; the hydrophobic composite gel was transferred to a high-pressure reaction kettle, absolute ethanol was added to submerge the gel, and the air in the kettle was replaced with nitrogen three times, each time for 30 s; the reaction kettle was placed in a 5 °C low-temperature tank, and liquid CO2 with a purity of 99.9% was slowly injected into the reaction kettle at a rate of 0.5 MPa / min until the pressure reached 6 MPa; after standing for 1 h, 10 mL of the mixture was discharged, and the injection-discharge operation was repeated three times; the discharge valve was closed, the temperature was increased to 35 °C, CO2 was added at the same time until the pressure reached 9 MPa, the system was maintained in this state for 2 h, the pressure was slowly reduced to atmospheric pressure at a rate of 0.2 MPa / h, and the dry composite block was obtained after natural cooling to room temperature; the dried composite block was placed in an agate mortar and manually ground until no obvious clumps were formed; the planetary ball mill (agate balls, ball-to-material ratio of 5:1) was used to grind the mixture at a rotation speed of 300 rpm for 10 min, and the glass bead reinforced aerogel composite particles were obtained by sieving through a 100-500 mesh screen.
[0042] Preparation Example 2
[0043] This preparation example is basically the same as Preparation Example 1, except that in step (2), 25 g of silica sol with a particle size of 10-20 nm and a solid content of 25% was slowly poured into 75 g of activated microbeads at a rate of 5 mL / min, the system was stirred at a rotation speed of 400 rpm for 30 min, 25 wt% ammonia water was added at a rate of 2 drops / s, the pH of the system was adjusted to 9, the system was continuously stirred for 10 min, and then the composite wet gel was transferred to a polytetrafluoroethylene mold, sealed, and allowed to stand at room temperature for 2 h.
[0044] Preparation Example 3
[0045] This preparation example is basically the same as Preparation Example 1, except that in step (2), 83.3 g of silica sol with a particle size of 10-20 nm and a solid content of 15% was slowly poured into 16.7 g of activated microbeads at a rate of 5 mL / min, the system was stirred at a rotation speed of 400 rpm for 30 min, 25 wt% ammonia water was added at a rate of 2 drops / s, the pH of the system was adjusted to 10, the system was continuously stirred for 10 min, and then the composite wet gel was transferred to a polytetrafluoroethylene mold, sealed, and allowed to stand at room temperature for 2 h.
[0046] Preparation Example 4
[0047] The present preparation example is basically the same as Preparation Example 1, except that in step (3): 100 mL of deionized water was mixed with anhydrous ethanol in a volume ratio of 9:1 to obtain an aging solution; 20 g of the composite wet gel was completely immersed in 100 mL of the aging solution, and after sealing, it was placed in a 60°C constant temperature water bath and aged for 24 h (the aging solution was replaced every 8 h during the period); 100 mL of n-hexane was taken, 1 g of trimethylchlorosilane was added, and it was stirred uniformly to obtain a modifier solution; in a fume hood, the composite gel was rinsed with anhydrous ethanol twice, and then it was transferred to the modifier solution and reacted at 50°C under magnetic stirring at a rotation speed of 200 rpm for 4 h; after the reaction was completed, the product was soaked with anhydrous ethanol three times, each time for 100 mL and 2 h, to obtain a hydrophobic composite gel; the hydrophobic composite gel was transferred to a high-pressure reaction kettle, anhydrous ethanol was added to submerge the gel, and the air in the kettle was replaced with nitrogen three times, each time for 30 s; the reaction kettle was placed in a 3°C low-temperature tank, and pure liquid CO2 with a purity of 99.9% was slowly injected into the kettle at a rate of 0.5 MPa / min until the pressure reached 5 MPa; after standing for 1 h, 10 mL of the mixed solution was discharged, and the injection-discharge operation was repeated three times; the discharge valve was closed, the temperature was raised to 32°C, and at the same time, CO2 was supplemented until the pressure reached 8 MPa; the state was maintained for 1.5 h, the temperature was kept at 32°C, and the pressure was slowly reduced to atmospheric pressure at a rate of 0.1 MPa / h; after natural cooling to room temperature, the dry composite block was taken out; the dried composite block was placed in an agate mortar and manually ground until there were no obvious lumps; then a planetary ball mill (agate balls, ball-to-material ratio of 5:1) was used to grind for 10 min at a rotation speed of 300 rpm, and the glass bead reinforced aerogel composite particles were obtained by passing through a 100-500 mesh sieve.
[0048] Preparation Example 5
[0049] The preparation example is basically the same as preparation example 1, except that: step (3): 100 mL of deionized water is mixed with anhydrous ethanol to obtain an aging solution; 20 g of the composite wet gel is completely soaked in 100 mL of the aging solution, sealed and placed in a 60℃ constant temperature water bath, and aged for 24 h (the aging solution is replaced every 8 h during the period) to obtain a composite gel; 100 mL of cyclohexane is taken, 4 g of methyltrioxysilane is added, and the mixture is stirred uniformly to obtain a modifier solution; in a fume hood, the composite gel is rinsed with anhydrous ethanol twice, transferred to the modifier solution, and stirred at 200 rpm and 50℃ for 4 h; after the reaction is completed, the product is soaked with anhydrous ethanol three times, 100 mL each time, for 2 h each time, to obtain a hydrophobic composite gel; the hydrophobic composite gel is transferred to a high-pressure reaction kettle, anhydrous ethanol is added to submerge the gel, and the kettle is replaced with nitrogen three times, 30 s each time; the reaction kettle is placed in an 8℃ low-temperature tank, and pure liquid CO2 with a purity of 99.9% is slowly injected at a rate of 0.5 MPa / min until the pressure reaches 5 MPa; after standing for 1 h, 10 mL of the mixture is discharged, and the injection-discharge operation is repeated three times; the discharge valve is closed, the temperature is raised to 40℃, and CO2 is supplemented to a pressure of 10 MPa; the state is maintained for 3 h, the temperature is maintained at 40℃, and the pressure is slowly reduced to atmospheric pressure at a rate of 0.3 MPa / h; after natural cooling to room temperature, the dry composite block is taken out to obtain a glass bead reinforced aerogel composite particle.
[0050] Preparation example 6
[0051] The preparation example is basically the same as preparation example 1, except that: step (1): hollow glass microbeads with a particle size of 10-30 μm are placed in a plasma jet with a current of 6A, and stay for 2 s to ensure uniform exposure of the surface within 2 s; the gas source pressure is 3.5 kgf / cm 2, the processing width is 50 mm to obtain the surface-treated hollow glass microspheres; 100 g of the surface-treated hollow glass microspheres is added into 500 mL of anhydrous ethanol, and ultrasonic cleaning is performed at a power of 300 W for 30 min; after filtration, the obtained product is washed twice with deionized water, and vacuum drying is performed at a vacuum degree of 0.09 MPa and a temperature of 60 ℃ for 2 h to obtain the pretreated glass microspheres; 300 mL of anhydrous ethanol is added into a three-necked flask, and 3 g of KH550 is slowly added dropwise at a speed of 1 drop / s under stirring, 5 mL of deionized water is added dropwise, and the pH of the system is adjusted to 4 by using 0.1 mol / L hydrochloric acid; the stirring is continued for 10 min to obtain a coupling agent solution; the pretreated glass microspheres are added into the coupling agent solution, the temperature is increased to 70 ℃, and the reaction is performed at a magnetic stirring speed of 300 rpm for 3 h; after the reaction is completed, the product is filtered, washed three times with anhydrous ethanol, and transferred to a vacuum drying oven, and vacuum drying is performed at a temperature of 60 ℃ and a vacuum degree of 0.09 MPa for 4 h to obtain the activated microspheres.
[0052] Preparation Example 7
[0053] The preparation example is basically the same as Preparation Example 6, except that in step (1), 100 g of borosilicate glass powder with a particle size of 1-5 μm and 1 g of sodium polycarboxylate are added into 200 g of deionized water, and the mixture is ground by using a planetary ball mill (marble balls, ball-to-material ratio 5:1) for 1 h to obtain a uniform glass powder suspension at a rotation speed of 300 rpm; 15 g of a double-bubble surfactant emulsion with a solid content of 30% and a particle size of 5-10 μm is slowly added into the suspension under stirring, and the stirring is continued for 30 min to form a stable mixed slurry, which is then sieved through a 100-mesh sieve for standby use; a spray dryer is started, and preheating is performed to an inlet air temperature of 200 ℃ and an outlet air temperature of 80 ℃; the above-mentioned slurry is added into the spray dryer at a feeding rate of 5 mL / min, and the mixture is dispersed into droplets at a rotation speed of 15,000 rpm; the precursor microspheres are formed in the drying chamber, and then enter a cyclone separator; the particles with a particle size of 10-50 μm are collected after sieving through a 50-200 mesh sieve; the above-mentioned particles are placed in a box-type atmosphere furnace, and the temperature is increased to 600 ℃ at a heating rate of 5 ℃ / min under nitrogen protection; the temperature is maintained at 600 ℃ for 3 h, and then the temperature is increased to 1,200 ℃ at a heating rate of 3 ℃ / min, and the temperature is maintained at 1,200 ℃ for 2 h; the furnace is naturally cooled to room temperature to obtain double-cavity hollow glass microspheres; the double-cavity hollow glass microspheres are placed in front of a plasma jet with a current of 6 A, and the residence time is 2 s to ensure that all the surfaces are uniformly exposed within 2 s; the gas source pressure is 3.5 kgf / cm 2, the power is 1000W, the processing width is 50mm to obtain the surface treated hollow glass beads; 100g of the surface treated hollow glass beads is added into 500mL of anhydrous ethanol, and ultrasonic cleaning is performed at a power of 300W for 30min; after filtration, the obtained product is washed twice with deionized water, and vacuum drying is performed at a vacuum degree of 0.09MPa and a temperature of 60℃ for 2h to obtain the pretreated glass beads; 300mL of anhydrous ethanol is added into a three-necked flask, 3g of KH550 is slowly added at a speed of 1drop / s under stirring, 5mL of deionized water is added dropwise, the pH of the system is adjusted to 4 by using 0.1mol / L hydrochloric acid, and stirring is continued for 10min to obtain a coupling agent solution; the pretreated glass beads are added into the coupling agent solution, the temperature is increased to 70℃, and the reaction is performed at a magnetic stirring speed of 300rpm for 3h; after the reaction is completed, the product is filtered, washed with anhydrous ethanol for 3 times, and transferred to a vacuum drying oven, and vacuum drying is performed at a temperature of 60℃ and a vacuum degree of 0.09MPa for 4h to obtain the activated beads.
[0054] Example 1
[0055] The example provides a PPR water supply heat preservation pipe, which comprises 7.5kg of PPR resin, 2.5kg of glass bead reinforced aerogel composite particles and 0.03kg of vinyl trimethoxysilane, wherein the glass bead reinforced aerogel composite particles are obtained by using the method in the preparation example 1.
[0056] The example also provides a preparation method of the PPR water supply heat preservation pipe, which comprises the following steps:
[0057] The raw materials are weighed according to the formula and uniformly mixed to obtain a mixture;
[0058] The mixture is sent into a double-screw extruder for granulation, and the process parameters are set as follows: the temperature of zone 1 is 160-170℃, the temperature of zone 2 is 170-180℃, the temperature of zone 3 is 180-190℃, the temperature of zone 4 is 185-195℃, the temperature of the die head is 190-200℃, the screw rotation speed is 350r / min, and the vacuum degree is-0.07MPa; after extrusion, the product is water-cooled and cut into particles to obtain the composite master batch;
[0059] The composite master batch is added into a single-screw extruder, and the extrusion temperature is controlled in sections as follows: the temperature of the feeding section is 170-180℃, the temperature of the compression section is 180-190℃, the temperature of the homogenization section is 190-200℃, and the temperature of the die head is 200-210℃; the screw rotation speed is 70r / min; a PPR pipe mold is used, the melt is extruded through the mold and then enters a vacuum setting box, and the pipe is cooled and set under a vacuum degree of 0.05MPa; the cooling water temperature is controlled at 25℃; the pipe after setting is pulled by a traction machine at a speed of 2m / min, and then cut into pipes of a set length by a planetary cutting machine to obtain the PPR water supply heat preservation pipe.
[0060] Example 2
[0061] The embodiment is basically the same as embodiment 1, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles and 0.02 kg of vinyl trimethoxysilane, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 1.
[0062] Example 3
[0063] The embodiment is basically the same as embodiment 1, except that the PPR water supply heat preservation pipe of the embodiment comprises 8.5 kg of PPR resin, 1.5 kg of glass bead reinforced aerogel composite particles and 0.01 kg of vinyl trimethoxysilane, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 1.
[0064] Example 4
[0065] The embodiment is basically the same as embodiment 1, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzaldehyde sorbitol and 0.01 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 1.
[0066] Example 5
[0067] The embodiment is basically the same as embodiment 1, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzaldehyde sorbitol and 0.02 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 1.
[0068] Example 6
[0069] The embodiment is basically the same as embodiment 1, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzaldehyde sorbitol and 0.03 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 1.
[0070] Example 7
[0071] The embodiment is basically the same as embodiment 5, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzal sorbitol, and 0.02 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 2.
[0072] Embodiment 8
[0073] The embodiment is basically the same as embodiment 5, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzal sorbitol, and 0.02 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 3.
[0074] Embodiment 9
[0075] The embodiment is basically the same as embodiment 5, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzal sorbitol, and 0.02 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 4.
[0076] Embodiment 10
[0077] The embodiment is basically the same as embodiment 5, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzal sorbitol, and 0.02 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 5.
[0078] Embodiment 11
[0079] The embodiment is basically the same as embodiment 5, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzal sorbitol, and 0.02 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the product of preparation example 6.
[0080] Embodiment 12
[0081] The embodiment is basically the same as embodiment 5, except that the PPR water supply heat preservation pipe of the embodiment comprises 8 kg of PPR resin, 2 kg of glass bead reinforced aerogel composite particles, 0.02 kg of vinyl trimethoxysilane, 0.01 kg of cyclohexyl-substituted benzaldehyde sorbitol, and 0.02 kg of lanthanum stearate, wherein the glass bead reinforced aerogel composite particles are obtained by using the preparation example 7.
[0082] Comparative example 1
[0083] The present comparative example provides a preparation method of a PPR water supply heat preservation pipe, comprising the following steps:
[0084] The PPR resin is sent into a double-screw extruder for granulation, and the process parameters are set as follows: the temperature of zone 1 is 160-170℃, the temperature of zone 2 is 170-180℃, the temperature of zone 3 is 180-190℃, the temperature of zone 4 is 185-195℃, and the temperature of the die head is 190-200℃; the screw rotation speed is 350 r / min, the vacuum degree is-0.07 MPa, and the extruded product is cooled by water and then cut into granules to obtain the master batch;
[0085] The master batch is added into a single-screw extruder, and the extrusion temperature is controlled in sections as follows: the feeding section is 170-180℃, the compression section is 180-190℃, the homogenization section is 190-200℃, and the temperature of the die head is 200-210℃; the screw rotation speed is 70 r / min; a PPR pipe mold is used, the melt is extruded through the mold and then enters a vacuum setting box, cooled and set under a vacuum degree of 0.05 MPa, the cooling water temperature is controlled at 25℃, the pipe material after setting is pulled by a traction machine at a speed of 2 m / min, and then cut into a set length by a planetary cutting machine to obtain the PPR water supply pipe.
[0086] The PPR water supply heat preservation pipe is obtained after forming an integrally formed heat preservation layer on the surface of the obtained PPR water supply pipe by using polyurethane in-situ foaming.
[0087] Comparative example 2
[0088] The present comparative example is basically the same as embodiment 1, except that the PPR water supply heat preservation pipe of the present comparative example comprises 7.5 kg of PPR resin, 1.5 kg of silica aerogel, 1 kg of hollow glass beads, and 0.03 kg of vinyl trimethoxysilane.
[0089] The preparation method of the silica aerogel is as follows:
[0090] (1) 100 g of silica sol with a particle size of 10-20 nm and a solid content of 20% was stirred at 400 rpm for 30 min, 25 wt% ammonia was added to adjust the pH of the system to 9.5, and then the stirring was continued for 10 min before being transferred to a polytetrafluoroethylene mold. The wet gel was obtained after being left at room temperature for 2 h. Anhydrous ethanol and deionized water were mixed in a volume ratio of 9:1 to obtain an aging solution. 20 g of wet gel was completely immersed in 100 mL of aging solution, sealed and placed in a 60°C constant temperature water bath for 24 h to obtain a composite gel. 100 mL of anhydrous ethanol was taken and 3 g of hexamethyldisilazane was added and stirred uniformly to obtain a modifier solution. In a fume hood, the gel was washed with anhydrous ethanol twice and then transferred to the modifier solution and stirred at 200 rpm and 50°C for 4 h. After the reaction, the product was soaked in anhydrous ethanol for 3 times, each time for 2 h, to obtain a hydrophobic gel. The hydrophobic gel was transferred to a high-pressure reaction kettle, anhydrous ethanol was added to submerge the gel, and the kettle was purged with nitrogen for 3 times, each time for 30 s. The reaction kettle was placed in a 5°C low-temperature tank, and liquid CO2 with a purity of 99.9% was slowly injected into the kettle at a rate of 0.5 MPa / min until the pressure reached 6 MPa. After standing for 1 h, a small amount of mixed solution was discharged, and the injection-discharge operation was repeated 3 times. The discharge valve was closed, the temperature was raised to 35°C, and CO2 was added to maintain a pressure of 9 MPa. The temperature was maintained at 35°C for 2 h, and then the pressure was slowly reduced to atmospheric pressure at a rate of 0.2 MPa / h. After natural cooling to room temperature, the dry block was obtained. The dry block was placed in an agate mortar and manually ground until there were no obvious lumps. Then, a planetary ball mill (agate balls, ball-to-material ratio of 5:1) was used to grind the block at a speed of 300 rpm for 10 min, and then the glass bead reinforced aerogel composite particles were obtained by sieving through a 100-500 mesh sieve.
[0091] Detection standard:
[0092] Thermal insulation performance test:
[0093] 1. Thermal conductivity test: The PPR water supply heat preservation pipes prepared in Examples 1-12 and Comparative Examples 1-2 were tested for thermal conductivity λ0 according to GB / T10294-2008 "Determination of Steady-state Thermal Resistance and Related Properties of Thermal Insulation Materials by Guarded Hot Plate Method". The test results are recorded in Table 1.
[0094] 2. Long-term thermal stability test: simulate the change of thermal conductivity after long-term use, accelerate the degradation of material performance through thermal aging test, evaluate the durability of thermal insulation performance, specifically: the PPR water heating pipes prepared from examples 1-12 and comparative examples 1-2 are made into samples and placed in a thermal aging test box, the temperature is set to 95℃, and the test lasts for 1000h. After taking out the samples, they are placed in a standard environment (23±2℃, 50±5%RH) for 24h to restore to room temperature. According to the above thermal conductivity test procedure, the thermal conductivity λ1 of the aged samples is measured, and the thermal conductivity change rate is calculated as [ (λ1-λ0) / λ0] ×100%. The test results are recorded in Table 1.
[0095] Tensile strength test: according to GB / T1040.2-2006 "Test methods for plastics-determination of tensile properties-part 2: test conditions", the tensile strength σ0 and elongation at break ε0 of the PPR water heating pipes prepared from examples 1-12 and comparative examples 1-2 are tested, and the test results are recorded in Table 1.
[0096] Weather resistance test: the PPR water heating pipes prepared from examples 1-12 and comparative examples 1-2 are made into samples and placed in a thermal aging test box, the temperature is set to 100℃, and the test lasts for 336h. After taking out the samples, they are placed in a standard environment (23±2℃, 50±5%RH) for 24h to restore to room temperature. According to the above tensile strength test, the tensile strength σ t and elongation at break ε t of the aged samples are tested, and the tensile strength retention rate ησ= (σ t / σ0) ×100% and the elongation at break retention rate ηε= (ε t / ε0) ×100% are calculated. The test results are recorded in Table 1.
[0097] Table 1 Performance test data of PPR water heating pipes in examples 1-12 and comparative examples 1-2
[0098]
[0099] According to Table 1, combined with example 1 and comparative example 1, it can be seen that by adding glass bead reinforced aerogel composite particles to the PPR resin to prepare PPR water heating pipes, compared with the traditional outer polyurethane insulation layer, the problem of microcracks caused by the difference in thermal expansion coefficient between the two, and the penetration of oxygen along the cracks to accelerate the aging of PPR is overcome. Therefore, the PPR water heating pipes prepared in the present application not only have excellent thermal insulation properties, but also have good durability.
[0100] Referring to Table 1, combined with Example 1 and Comparative Example 2, it can be seen that the glass microsphere reinforced aerogel composite particles of the application compensate for the brittleness defect of aerogel by taking hollow glass microspheres as the mechanical skeleton, and the closed cavity structure helps to improve the overall thermal insulation; at the same time, the aerogel fills the gap between the microspheres to form a porous-cavity composite heat insulation network, which improves the comprehensive performance of the prepared PPR water supply heat preservation pipe compared with the scheme of adding hollow glass microspheres and silica aerogel physically mixed in the PPR resin.
[0101] Referring to Table 1, combined with Example 2 and 5, it can be seen that the application realizes the improvement of strength and stability by adding an appropriate amount of nucleating agent in the PPR water supply heat preservation pipe to optimize the crystalline structure.
[0102] Referring to Table 1, combined with Example 5 and 11, it can be seen that the application performs plasma surface treatment on the hollow glass microspheres, which can form active groups such as hydroxyl and carboxyl groups on the surface. These active groups react with silane coupling agents to anchor the groups of silane coupling agents on the surface of hollow glass microspheres, which is conducive to forming a firm structure with the aerogel network and improving the comprehensive performance of the prepared PPR water supply heat preservation pipe.
[0103] Referring to Table 1, combined with Example 11 and 12, it can be seen that the application prepares double-cavity hollow glass microspheres, which form an interpenetrating network with silica aerogel. In terms of mechanical strength, the interpenetrating network of double-cavity hollow glass microspheres can reduce local stress concentration and improve tensile strength compared with the interpenetrating network of single-cavity microsphere system, due to the multi-node stress dispersion of double-cavity structure, the synergistic anti-deformation of double cavities and the enhanced interface anchoring effect. In terms of thermal conductivity, the double thermal resistance formed by the double cavities, the more tortuous heat conduction path and the reduced thermal bridge effect between the microspheres make the thermal conductivity coefficient decrease, which improves the comprehensive performance of the prepared PPR water supply heat preservation pipe.
[0104] The specific embodiments are only an explanation of the application, which is not a limitation of the application. Those skilled in the art can make modifications to the embodiments without creative contribution after reading the specification, but as long as the modifications are within the scope of the claims of the application, they are protected by the patent law.
Claims
1. A PPR water heating pipe, characterized in that, The raw materials include the following components by weight: 75-85 parts of PPR resin, 15-25 parts of glass microsphere reinforced aerogel composite particles, and 0.1-0.3 parts of silane coupling agent; The preparation method of the glass microsphere reinforced aerogel composite particles is as follows: hollow glass microspheres are mixed with an ethanol solution containing a silane coupling agent, heated for reaction, and vacuum dried to obtain activated microspheres; silica aerogel precursor is added to the activated microspheres, and the pH is adjusted to 9-10 to form a gel by reaction; the gel is aged, hydrophobically treated, dried, and then crushed to obtain glass microsphere reinforced aerogel composite particles.
2. The PPR water heating pipe according to claim 1, characterized in that, The silica aerogel precursor is a silica sol with a particle size of 10-20 nm and a solid content of 15%-25%.
3. The PPR water heating pipe according to claim 1, characterized in that, The mass ratio of the silica aerogel precursor to the activated microspheres is (1-5):(1-3).
4. The PPR water heating pipe according to claim 1, characterized in that, The hydrophobic treatment specifically comprises the following steps: dissolving a modifier in a solvent to obtain a modified solution, and stirring the gel after aging in the modified solution to obtain a hydrophobic gel.
5. The PPR water heating pipe according to claim 1, characterized in that, The drying is performed by using a supercritical drying method, specifically as follows: the gel after hydrophobic treatment is placed in a high-pressure reaction kettle, the gel is covered with anhydrous ethanol, and nitrogen is introduced to replace the air in the kettle; the reaction kettle is placed in a low-temperature environment of 3-8℃, liquid CO2 is injected into the reaction kettle by a high-pressure pump to a pressure of 5-7 MPa, and the mixture containing ethanol is discharged after standing for 40-80 min; the injection-discharge operation is repeated multiple times; the temperature is increased to 32-40℃, and CO2 is added to increase the pressure to 8-10 MPa; after maintaining for 1.5-3 h, the pressure is reduced to atmospheric pressure at a rate of 0.1-0.3 MPa / h, and the gel is taken out after natural cooling.
6. The PPR water heating pipe according to claim 1, characterized in that, The hollow glass microspheres are hollow glass microspheres treated by plasma.
7. The PPR water heating pipe according to claim 1, characterized in that, The hollow glass microspheres are double-cavity hollow glass microspheres, and the specific preparation method is as follows: 100 parts by weight of borosilicate glass powder, 15-20 parts by weight of a double-cavity template agent, 1-2 parts by weight of a dispersing agent, and 200-300 parts by weight of deionized water are ball milled for 2-4 h to prepare a slurry; the slurry is added to a spray drying machine at a feeding rate of 5-10 mL / min, and is atomized into droplets under the conditions of 15000-20000 rpm, inlet air temperature of 200-220℃, and outlet air temperature of 80-100℃, and the precursor microspheres are formed after drying; the temperature is increased to 600-650℃ under nitrogen protection for 2-3 h for defatting, and then the temperature is increased to 1200-1300℃ for melting and sintering for 1-2 h, and the double-cavity hollow glass microspheres are obtained after natural cooling to room temperature.
8. The PPR water heating pipe according to claim 1, characterized in that, The raw materials further include 0.2-0.4 parts by weight of a nucleating agent.
9. The PPR water heating pipe according to claim 8, characterized in that, The nucleating agent is a mixture of sorbitol α nucleating agent and rare earth β nucleating agent at a mass ratio of 1:(1-3).
10. The method of claim 1-9 for making PPR water heating pipe, characterized in that, The method comprises the following steps: The raw materials are weighed according to the formula and mixed uniformly to obtain a mixture, the mixture is melt-extruded and pelletized to obtain a composite master batch, the composite master batch is melted and extruded through a mold, and then cooled and shaped to obtain a PPR water supply heat preservation pipe.
Citation Information
Patent Citations
PPR-PVC (polypropylene-polyvinyl chloride) water supply pipeline
CN103851273A
Hollow glass bead-aerogel composite material and preparation method thereof
CN114736035A
Low density particles for use in concrete and other mixtures
US20210009472A1